High Admission Glucose Is Associated With Poor Outcome After Endovascular Treatment for Ischemic Stroke. Issue 11 (November 2020) - Rinkel, Leon A.; Nguyen, T. Truc My; Guglielmi, Valeria; Groot, Adrien E.; Posthuma, Laura; Roos, Yvo B.W.E.M.; Majoie, Charles B.L.M.; Lycklama à Nijeholt, Geert J.; Emmer, Bart J.; van der Worp, H. Bart; Wermer, Marieke J.H.; Kruyt, Nyika D.; et al.
Abstract : Background and Purpose: High-serum glucose on admission is a predictor of poor outcome after stroke. We assessed the association between glucose concentrations and clinical outcomes in patients who underwent endovascular treatment. Methods: From the MR CLEAN Registry, we selected consecutive adult patients with a large vessel occlusion of the anterior circulation who underwent endovascular treatment and for whom admission glucose levels were available. We assessed the association between admission glucose and the modified Rankin Scale score at 90 days, symptomatic intracranial hemorrhage and successful reperfusion rates. Hyperglycemia was defined as admission glucose ≥7.8 mmol/L. We evaluated the association between glucose and modified Rankin Scale using multivariable ordinal logistic regression and assessed whether successful reperfusion (extended Thrombolysis in Cerebral Infarction 2b-3) modified this association. Results: Of 3637 patients in the MR CLEAN Registry, 2908 were included. Median admission glucose concentration was 6.8 mmol/L (interquartile range, 5.9–8.1) and 882 patients (30%) had hyperglycemia. Hyperglycemia on admission was associated with a shift toward worse functional outcome (median modified Rankin Scale score 4 versus 3; adjusted common odds ratio, 1.69 [95% CI, 1.44–1.99]), increased mortality (40% versus 23%; adjusted odds ratio, 1.95 [95% CI, 1.60–2.38]), and an increased risk of symptomatic intracranial hemorrhage (9% versus 5%; adjusted odds ratio, 1.94 [95% CI, 1.41–2.66]) compared with nonhyperglycemic patients. The association between admission glucose levels and poor outcome (modified Rankin Scale score 3–6) was J -shaped. Hyperglycemia was not associated with the rate of successful reperfusion nor did successful reperfusion modify the association between glucose and functional outcome. Conclusions: Increased admission glucose is associated with poor functional outcome and an increased risk of symptomatic intracranial hemorrhage after endovascular treatment. Abstract : Supplemental Digital Content is available in the text.